Pemberdayaan Komunitas Tukang Becak Bengawan Solo Kelurahan Bunulrejo Kota Malang Melalui Ekonomi Kreatif - Amri Amri; Rasyik Adila (Penerbit Widina, Widina Media Utama, 2022)
This assistance aims to how the mentoring process carried out can achieve the target of the wishes of the rickshaw community by maximizing the Assets and Bases they have through the creative economy. The mentoring method used in the community empowerment process is to use the ABCD Method, which is a method that is carried out by maximizing the potentials of the community to be accompanied. The results of this assistance resulted in a positive impact, namely the First several Bengawan Solo Rickshaw Maker Communities in Malang City had dared to make additional work by making handicrafts. The second is that one of the rickshaw-making communities dares to open a small coffee shop to encourage the family's economy by increasing work activities through selling coffee and fried foods. The third goal of community empowerment in this case the becak community in Bunulrejo Village, Malang City is successful to do which is evidenced through the willingness of rickshaw drivers to increase family income through the creative economy can be done, not only as a rickshaw driver whose income is low